Study of the possibilities of using the method structural engineering of multilayer periodic systems to increase the mechanical properties of the coating, used as a protective on the details of the steam turbine aggregates - Соболь, Олег Валентинович; Дмитрик, Виталий Владимирович; Погребной, Николай Андреевич; Ищенко, Григорий Иванович; Пинчук, Наталия Владимировна; Мейлехов, Андрей Александрович (Eastern-European Journal of Enterprise Technologies, 2015)
The technological conditions and structural condition necessary to obtain high mechanical properties of plasma-vacuum multilayer coatings built on a combination of solid (nitride) and plastic (metal) layers were considered. The advantages of using such a composition as a surface protective layer on parts of steam turbine units were analyzed. It is established that a negative bias potential applied to the substrate during deposition process leads to increased compressive stresses and the formation of preferential orientation of the crystallites in the layers of TiN with [111] axis. As a result there is an increase of hardness from 26 GPa (Us = -70 V) to 36 GPa (Us = -230 V). Using a structured approach, defined and justified optimal layer thickness Ti (30 nm) and TiN (300 nm), providing a combination of high hardness and high abrasion resistance of coatings of the multilayer TiN/Ti.